Cardiac MRI predictors of adverse outcomes in adults with a systemic right ventricle. (20th January 2022) - Lewis, Matthew J.; Van Dissel, Alexandra; Kochav, Jonathan; DiLorenzo, Michael P.; Ginns, Jonathan; Zemer‐Wassercug, Noa; Groenink, Maarten; Mulder, Barbara; Rosenbaum, Marlon
Abstract: Aims: Predicting risk in individuals with a systemic right ventricle (SRV) remains difficult. We assessed the value of cardiac MRI (CMR) for predicting death, heart transplantation (HT), or need for a ventricular assist device (VAD) in adults with D‐transposition of the great arteries (DTGA) post Mustard/Senning and in adults with congenitally corrected transposition of the great arteries (ccTGA) at two large academic centres. Methods and results: Between December 1999 and November 2020, 158 adult patients with an SRV underwent CMR. Indexed right ventricular end‐diastolic volume (RVEDVI), indexed right ventricular end‐systolic volume (RVESVI), right ventricular ejection fraction (RVEF), and right ventricular mass (RV mass) were determined by a core laboratory. Receiver operating curves, area under the curve (AUC), and cut‐points maximizing sensitivity and specificity for the endpoint for each CMR parameter were calculated. Over a median of 8.5 years, 21 patients (13%) met a combined endpoint of HT referral, VAD, or death. Each CMR parameter was significantly associated with the endpoint in both cohorts. The AUCs for RVEDVI, RVESVI, RVEF, and RV mass to predict the endpoint were 0.93, 0.90, 0.73, and 0.84 for DTGA and 0.76, 0.74, 0.71, and 0.74 for ccTGA, respectively. Optimized cut‐points for RVEDVI were calculated for DTGA and ccTGA and were 132 and 126 mL/m 2, respectively. RVEDVI cut‐points were simplified to 130 mL/m 2 for survival analysis, which was significantly associated with survival in both cohorts. Conclusions: Cardiac MRI parameters are associated with an increased risk of death, HT, or VAD in patients with an SRV and should be considered to facilitate risk stratification.